Quantum control of photodissociation by manipulation of bond softening - Natan, Adi; Lev, Uri; Prabhudesai, Vaibhav S.; Bruner, Barry D.; Strasser, Daniel; Schwalm, Dirk; Ben-Itzhak, Itzik; Heber, Oded; Zajfman, Daniel; Silberberg, Yaron (My University, 2012)
We present a method to control photodissociation by manipulating the bond-softening mechanism occurring in strong shaped laser fields, namely by varying the chirp sign and magnitude of an ultrashort laser pulse. Manipulation of bond softening is experimentally demonstrated for strong-field (1012–1013 W/cm2) photodissociation of H+2, exhibiting a substantial increase of dissociation by positively chirped pulses with respect to both negatively chirped and transform-limited pulses. The measured kinetic energy release and angular distributions are used to quantify the degree of dissociation control. The control mechanism is attributed to the interplay of dynamic alignment and chirped light induced potential curves.